Interaksi Struktur Modal, Ukuran Perusahaan, dan Kepemilikan Manajerial terhadap Nilai Perusahaan: Peran Moderasi Kepemilikan Institusional - Juanda Surya; Fitriani Prastiawati; Abdul Malik Fajri; Rizki Putri Nurita Fonna; Chairanisa Natasha Miraza (SUSTAINABLE, 2026)
This study investigates the effect of capital structure, firm size, and managerial ownership on firm value, with   institutional ownership as a moderating variable. Using a quantitative approach, the study analyzed secondary data from companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. A total of 638 firm-year observations were selected through purposive sampling and analyzed using the SEM-PLS method. The findings show that capital structure does not significantly affect firm value, indicating that debt levels are not the main consideration for investors. Meanwhile, firm size and managerial ownership have a significant negative effect on firm value, suggesting that larger companies and higher managerial ownership may indicate inefficiency or managerial entrenchment. In addition, institutional ownership does not moderate the relationship between capital structure and managerial ownership on firm value. The study concludes that internal company factors play a more dominant role in determining firm value than external monitoring mechanisms